(untitled) (Communications in Computational Physics, 2023)
New superconvergent structures are proposed and analyzed for the finite volume element (FVE) method over tensorial meshes in general dimension d (for d≥2); we call these orthogonal superconvergent structures. In this framework, one has the freedom to choose the superconvergent points of tensorial k-order FVE schemes (for k≥3). This flexibility contrasts with the superconvergent points (such as Gauss points and Lobatto points) for current FE schemes and FVE schemes, which are fixed. The orthogonality condition and the modified M-decomposition (MMD) technique that are developed over tensorial meshes help in the construction of proper superclose functions for the FVE solutions and in ensuring the new superconvergence properties of the FVE schemes. Numerical experiments are provided to validate our theoretical results.